2021
DOI: 10.1007/s10959-021-01095-4
|View full text |Cite
|
Sign up to set email alerts
|

Weak Convergence of Topological Measures

Abstract: Topological measures and deficient topological measures are defined on open and closed subsets of a topological space, generalize regular Borel measures, and correspond to (nonlinear in general) functionals that are linear on singly generated subalgebras or singly generated cones of functions. They lack subadditivity, and many standard techniques of measure theory and functional analysis do not apply to them. Nevertheless, we show that many classical results of probability theory hold for topological and defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Theorem 1 in this article is a modification of Theorem 2.1 and 2.2 in [8]. Theorem 2.1 and 2.2 in [8] require non-negative functions f. Theorem 3 is a generalization of Corollary 1. Corollary 1 is the main result in [1].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Theorem 1 in this article is a modification of Theorem 2.1 and 2.2 in [8]. Theorem 2.1 and 2.2 in [8] require non-negative functions f. Theorem 3 is a generalization of Corollary 1. Corollary 1 is the main result in [1].…”
Section: Discussionmentioning
confidence: 91%
“…There is a rich bibliography concerning the convergence of sequences of measures, besides the above-mentioned studies [1-3]; see, for example, [4][5][6][7][8].…”
Section: Introduction and Terminologymentioning
confidence: 99%
“…In other words, the topological determination of measure compactness becomes simpler in this setting. It is shown that topological measures and deficient measures may not always support subadditivity and the properties of linear functionals while admitting the weak convergence of topological measures, which is a variety of Alexandrov weak convergence [9]. Interestingly, if we consider a ring of sets σ(A) and a topological vector space X, then the measure µ : σ(A) → X may show strong convergence to zero if µ( B n i=1 ) → 0 in σ(A) where the sets in sequence B n i=1 under measure are disjoint [10].…”
Section: Motivation and Contributionsmentioning
confidence: 99%